Managing the heart of the university: Dean’s offices in the process of changes. New legal and organizational reality - Jaskólska, Justyna (Przegląd Krytyczny, 2022)
A major reform of the higher education system began with the entry into force of the Law on higher education and science act (from October 1, 2018), aimed at improving conditions for practicing scientific and didactic excellence in Polisch universities. The changes in the regulations concerned the organization of universities and ensuring the sustainable development of academic centers across the country, which influenced the model of university management after 2018. The edited volume entitled Dean’s offices in the process of changes. New legal and organizational reality was written at this critical time of major changes in Polish higher education, and it provides a timely and thorough overview of the implications of the reform, especially regarding the management practices.